Synthesis, characterization and photocatalytic activity of novel mixed metal oxides/reduced graphene oxide hybrid catalysts - Nha Khanh, Dang Nguyen; Mai Tho, Nguyen Thi; Thang, Nguyen Quoc; Tien, Nguyen Thanh; Phong, Chau Tan; Cang, Mai Quynh; Kim Phuong, Nguyen Thi (Vietnam Journal of Science and Technology, 2019)
A novel ZnBi2O4/rGO hybrid catalysts had been synthesized by a simple precipitation method. The crystallinity, structural, and morphological features were studied by XRD, FE-SEM and UV-Vis diffused reflectance  techniques. The photocatalytic activity of ZnBi2O4/rGO catalysts were evaluated by degradation of Indigo Carmine dye under visible-light irradiation. The enhancement of photocatalytic properties of ZnBi2O4/rGO attributed to the synergistic effect between ZnBi2O4 and rGO, which effectively separation of the photogenerated electron-hole pairs in ZnBi2O4. Moreover, the obtained ZnBi2O4/rGO displayed high chemical stability after four consecutive experiments under visible light.